Taktyczna broń nuklearna w Europie - Kopeć, Rafał (Przegląd Strategiczny, 2016)
Tactical nuclear weapons were quantitatively a dominant class o f nuclear weapons in the Cold War. However, currently, they stay on the margin of strategic thinking. The aim o f the article is to provide a reader with an insight into the issues related to tactical nuclear weapons in the European NATO countries (however, they are primarily American weapons). The article defines the term „tactical nuclear weapons” and provides an overview of these weapons. It stresses the reasons o f their development by the Western countries in the Cold War. The paper focuses on the nuclear sharing NATO program (but French non-strategic weapons are also mentioned) - its principles, current status and prospects, including controversies around the future o f tactical nuclear weapons in Europe.